2015
DOI: 10.1039/c5lc00454c
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalized medicine: chemosensitivity assays of patient lung cancer cell spheroids in a perfused microfluidic platform

Abstract: Cancer is responsible for millions of deaths worldwide and the variability in disease patterns calls for patient-specific treatment. Therefore, personalized treatment is expected to become a daily routine in prospective clinical tests. In addition to genetic mutation analysis, predictive chemosensitive assays using patient's cells will be carried out as a decision making tool. However, prior to their widespread application in clinics, several challenges linked to the establishment of such assays need to be add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 31 publications
1
95
0
1
Order By: Relevance
“…While some screening and diagnostic devices target biomolecules or proteins, others isolate exfoliated tumor cells [80] and nucleic acid-containing vesicles [81]; this genetic material could provide a starting point for downstream genetic analyses to inform treatment decisions and provide insights into bladder cancer development and variants without requiring expensive and invasive biopsy procedures. In studies on lung [126] and breast cancer [127], microfluidic devices for mimicking tumor microenvironments provide a path toward tailored treatment approaches, while single-cell 'omics' analysis yields invaluable insight into the heterogeneity and molecular processes of cancer [128]. This is especially important in addressing inter-patient tumor heterogeneity [129].…”
Section: Resultsmentioning
confidence: 99%
“…While some screening and diagnostic devices target biomolecules or proteins, others isolate exfoliated tumor cells [80] and nucleic acid-containing vesicles [81]; this genetic material could provide a starting point for downstream genetic analyses to inform treatment decisions and provide insights into bladder cancer development and variants without requiring expensive and invasive biopsy procedures. In studies on lung [126] and breast cancer [127], microfluidic devices for mimicking tumor microenvironments provide a path toward tailored treatment approaches, while single-cell 'omics' analysis yields invaluable insight into the heterogeneity and molecular processes of cancer [128]. This is especially important in addressing inter-patient tumor heterogeneity [129].…”
Section: Resultsmentioning
confidence: 99%
“…Microwells [8,25,[87][88][89] and U-shaped microstructures [21,64,[90][91][92][93] have been designed for spheroid formation and culture in microfluidic platforms. These structures facilitate short-term [23,94], controllable and uniform diameter [22,95] and compact spheroid generation [32,92].…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
“…Forming cellular aggregates and making compact spheroids within the first days is called the first phase. Spheroid diameter decreases during the first phase because cells are attaching to each other and forming stable aggregates [25], Figure 2A. The duration time of the first phase depends on the cell type as well as the method used.…”
Section: Spheroid Formation Phasesmentioning
confidence: 99%
“…After the injection of anticancer drug 5-fluorouracil (5-FU), the dynamic changes on the metabolic activity of the cells in response to the drug could be monitored and analyzed continuously (Kwapiszewska et al, 2014). Ruppen et al observed a higher chemoresistance in primary co-culture 33 spheroids (i.e., primary lung cancer epithelial cells and primary pericytes) than in primary monoculture spheroids in a Lung-on-a-Chip model, which could serve as a more chemosensitive tumor model (Ruppen et al, 2015). More deep understanding about tumors is expected to be unveiled as the tumor-on-a-chip technique develops, which will contribute enormously to drug and nanocarrier designing, screening, and evaluation.…”
Section: Cell Culture For Tumor-on-a-chipmentioning
confidence: 99%
“…Skin melanoma -Association between cancer and immune system (Businaro et al, 2013) Colon cancer Anticancer drugs (e.g., 5-fluorouracil) Anticancer efficacy; drug screening (Kwapiszewska et al, 2014) Breast cancer -Invasion (Trietsch et al, 2013) Photosensitizer (e.g., 5-aminolevulinic acid) and gold nanoparticles Photodynamic therapy evaluation (Yang et al, 2015) Lung cancer Anticancer drugs (e.g., gefitinib and masitinib) Anticancer efficacy; drug screening (Aref et al, 2013) Cisplatin Chemosensitivity evaluation (Ruppen et al, 2015) Brain glioma Anticancer drugs (e.g., vincristine and bleomycin)…”
mentioning
confidence: 99%